Depression to Cold War : a history of America from Herbert Hoover to Ronald Reagan - Siracusa, Joseph M. (Perspectives on the twentieth century., 2002)
Organized around the office of the president, this study focuses on American behavior at home and abroad from the Great Depression to the onset of the end of the Cold War, two key points during which America sought a re-definition of its proper relationship to the world. Domestically, American society continued the process of industrialization and urbanization that had begun in the 19th century. Urban growth accompanied industrialism, and more and more Americans lived in cities. Because of industrial growth and the consequent interest in foreign markets, the United States became a major world power. American actions as a nation, whether as positive attempts to mold events abroad or as negative efforts to enjoy material abundance in relative political isolation, could not help but affect the course of world history.